The association between low-dose aspirin intake and osteoarthritis: a population-based cross-sectional study based on NHANES - Xiong, Binglang; Zhang, Cheng; Cao, Xuhan; Guo, Ziyan; Bai, Zixing; Sun, Weidong (Frontiers in Medicine, 2024)
Objectives Low-dose aspirin is widely used as a preventive medication for cardiovascular diseases. However, there is controversy regarding the impact of low-dose aspirin on articular cartilage. The aim of this study is to explore the association between low-dose aspirin intake and osteoarthritis (OA). Methods We conducted a cross-sectional study based on the United States population data from the National Health and Nutrition Examination Survey (NHANES) 2011–2018. The investigation of low-dose aspirin intake and the diagnosis of OA was based on self-reporting in questionnaires. Multivariate regression models was used to assess the relationship between low-dose aspirin intake and OA. In addition, subgroup and interaction analysis were performed to assess the robustness of the results. Results A total of 12,215 participants were included in this study. Multivariate logistic regression analysis showed that low-dose aspirin use had significantly increased the odds of OA (OR = 1.14; 95% CI: 1.01–1.28; p = 0.035). A significant and consistent association of low-dose aspirin intake with OA was still observed in each subgroup stratified by gender, age, and the presence of comorbidities including diabetes, coronary heart disease, hypertension, and stroke. The results illustrated that the relationship between low-dose aspirin intake and OA was stable in all subgroups and had no interaction. Conclusion Our study confirmed that low-dose aspirin intake may increase the risk of OA. Attention should be paid to the possibility of joint degenerative changes in patients who take low-dose aspirin chronically. However, further studies are needed to explore the possible mechanisms behind this association.